If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 10)(4x + -10) = 0 Reorder the terms: (10 + 5x)(4x + -10) = 0 Reorder the terms: (10 + 5x)(-10 + 4x) = 0 Multiply (10 + 5x) * (-10 + 4x) (10(-10 + 4x) + 5x * (-10 + 4x)) = 0 ((-10 * 10 + 4x * 10) + 5x * (-10 + 4x)) = 0 ((-100 + 40x) + 5x * (-10 + 4x)) = 0 (-100 + 40x + (-10 * 5x + 4x * 5x)) = 0 (-100 + 40x + (-50x + 20x2)) = 0 Combine like terms: 40x + -50x = -10x (-100 + -10x + 20x2) = 0 Solving -100 + -10x + 20x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '10'. 10(-10 + -1x + 2x2) = 0 Factor a trinomial. 10((-2 + -1x)(5 + -2x)) = 0 Ignore the factor 10.Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(5 + -2x)' equal to zero and attempt to solve: Simplifying 5 + -2x = 0 Solving 5 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 0 + -5 -2x = 0 + -5 Combine like terms: 0 + -5 = -5 -2x = -5 Divide each side by '-2'. x = 2.5 Simplifying x = 2.5Solution
x = {-2, 2.5}
| x+(12+x)=150 | | -5r-18r-(-16r)=14 | | secx/cosx-tanx/cotx=1 | | (6y-9)=-2y+13(3) | | 3y-14=22-y | | 8x-1=5x-22 | | 19.57=2s+4.61 | | 8v+11-3b=2b+2 | | (13s+7)(6s-18)=0 | | 3/4--1/2 | | 20y+y+4y-22y-2y=6 | | 15-3x=40 | | 6=m-(3+2m) | | 2(x+6)-5=16 | | -16x^2+66x+13=0 | | 13-3p=-8p-15-7 | | 2x^4-2x-1=0 | | (6x-7)-(8x+5)=0 | | 8x^2-43x-18=0 | | 4(7x+3)-6=28x+6 | | (2t^3-3t^2+5t)-(6t^3+3t^2-5t+8)= | | t=3c-2d | | 4n-19n+12n=18 | | 5/6x-1=-7 | | -4.5y=-11.7 | | 2x+3y=10x+11 | | 3x-16-5x=40 | | y=-0.4x-2.1 | | 6*x=1500 | | 16s-4s-12s+3s=15 | | 0.66x+1=0.50 | | ln(5x+1)=ln(x+11) |